The Role of PGC-1α/UCP2 Signaling in the Beneficial Effects of Physical Exercise on the Brain - de Oliveira Bristot, Viviane José; de Bem Alves, Ana Cristina; Cardoso, Liziane Rosa; da Luz Scheffer, Débora; Aguiar, Aderbal Silva (Frontiers in Neuroscience, 2019)
In understanding the pathology of neurological diseases, the role played by brain energy metabolism is gaining prominence. Animal models have demonstrated that regular physical exercise improves brain energy metabolism while also providing antidepressant, anxiolytic, antioxidant and neuroprotective functions. This review summarizes the latest evidence on the roles played by peroxisome proliferator-activated receptor gamma (PPAR-) coactivator 1-alpha (PGC-1α) and mitochondrial uncoupling protein (UCP) in this scenario. The beneficial effects of exercise seem to depend on crosstalk between muscles and nervous tissue through the increased release of muscle irisin during exercise.